SARS-CoV-2 DNA Vaccine INO-4800 Induces Durable Immune Responses Capable of Being Boosted in a Phase 1 Open-Label Trial. (25th January 2022) - Kraynyak, Kimberly A; Blackwood, Elliott; Agnes, Joseph; Tebas, Pablo; Giffear, Mary; Amante, Dinah; Reuschel, Emma L; Purwar, Mansi; Christensen-Quick, Aaron; Liu, Neiman; Andrade, Viviane M; Diehl, Malissa C; et al.
Abstract: Background: Additional severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines that are safe and effective as primary vaccines and boosters remain urgently needed to combat the coronavirus disease 2019 (COVID-19) pandemic. We describe safety and durability of immune responses following 2 primary doses and a homologous booster dose of an investigational DNA vaccine (INO-4800) targeting full-length spike antigen. Methods: Three dosage strengths of INO-4800 (0.5 mg, 1.0 mg, and 2.0 mg) were evaluated in 120 age-stratified healthy adults. Intradermal injection of INO-4800 followed by electroporation at 0 and 4 weeks preceded an optional booster 6–10.5 months after the second dose. Results: INO-4800 appeared well tolerated with no treatment-related serious adverse events. Most adverse events were mild and did not increase in frequency with age and subsequent dosing. A durable antibody response was observed 6 months following the second dose; a homologous booster dose significantly increased immune responses. Cytokine-producing T cells and activated CD8 + T cells with lytic potential were significantly increased in the 2.0-mg dose group. Conclusions: INO-4800 was well tolerated in a 2-dose primary series and homologous booster in all adults, including elderly participants. These results support further development of INO-4800 for use as primary vaccine and booster. Clinical Trials Registration: NCT04336410. Abstract : Two-milligram dose of INO-4800, DNA-based vaccine encoding SARS-CoV-2 spike protein, appears safe and well tolerated and elicits humoral and cell-mediated immunity persisting to 6 months after a second dose. A third dose 6–10.5 months later significantly boosts immune responses.